Hydrogen embrittlement of ultra high strength 300 grade maraging steel - Santos, Luis Paulo Mourão dos (2015)
Slow strain rate tests were conducted in air and aqueous 0.6 M NaCl at −1.2 VSCE environments to investigate hydrogen embrittlement (HE) of ultra high strength 300 grade maraging steel. The results showed that the samples were susceptible to HE in different levels after submitted to heat treatments. Moreover, the over-aged samples were more resistant to HE than the peak-aged ones. Reverted austenite contained on the microstructure increased the fracture toughness of the material. EBSD revealed that the paths for intergranular crack propagation were mainly along grain boundaries with {001}//ND fiber orientation, while {111} and {110}//ND fibers were resistant to propagation.